THE INFLUENCE OF TAX KNOWLEDGE, PROFESSIONAL RECOGNITION, AND JOB MARKET CONSIDERATIONS ON CAREER CHOICE AS TAX CONSULTANTS OF ACCOUNTING STUDENTS IN THE SURAKARTA AREA - Mei Puspitasari; Suyatmin Waskito Adi (University of Darussalam Gontor, 2024)
Porpuse: This study aims to analyze whether Tax Knowledge, Professional Recognition, and Job Market Considerations affect the interest of accounting students in choosing to work as tax consultants. The type of research used is quantitative research through a questionnaire survey approach of accounting students. The sampling technique uses the Solvin method to determine the number of samples. Data collection was carried out using a questionnaire survey method via a Google form filled out by respondents. The research sample used was 120 respondents of accounting students from UMS, UNS, UNIBA, UNISRI, STIE in 2020-2021. In this study, the test used in the statistical analysis was hypothesis testing with quantitative data analysis and using the SPSS 26 program to test the data. Based on the results of management, the results of this study indicate that (1) tax knowledge affects the choice of a career as a tax consultant. (2) professional recognition affects the choice of a career as a tax consultant. (3) job market considerations affect the choice of a career as a tax consultant.